Canine Parvovirus ns1 gene and Chicken Anemia vp3 gene induce partial oncolysis of Canine Transmissible Venereal Tumor. Issue 1 (December 2017) - Bhat, Aubid; Ganguly, Bhaskar; Tiwari, Ashok; Das, Arup
Abstract The oncolytic effect of Canine Parvovirusns1 gene and Chicken Anemiavp3 gene in naturally occurring cases of Canine Transmissible Venereal Tumor (CTVT) is being reported. Dogs suffering from CTVT (N = 18) were systematically randomized into three groupsviz . A, B, and C (n = 6). Animals of the groups A, B, and C received 100 µg of thens1 gene, vp3 gene, andns1  +  vp3 gene combination, respectively, for three weeks intratumorally at weekly intervals; results were normalized against base values before commencement of therapy and after complete remission that were taken as negative and positive controls, respectively. Initiation of oncolytic gene therapy arrested the further progression of the tumor but most of the animals in the study underwent incomplete remission, indicating incomplete activity ofns1 andvp3 genes. The oncolytic effect of the treatments was in the orderns1  > vp3  > ns1  + vp3 . Oncolysis was accompanied by decreased mitotic index and AgNOR count, and increased TUNEL positive cells and CD4+ lymphocyte counts. Our findings show that Canine Parvovirusns1 may eventually find an important role as an oncolytic agent.